Produção de base ecológica : reconexão da produção e consumo no Litoral Norte do Rio Grande do Sul - Daniela Garcez Wives; João Armando Dessimon Machado; Marlise Amália Reinehr Dal Forno; Luciano Silva Figueiredo; Gabriela Coelho-de-Souza (Confins)
This paper analyzes the relationship between production and consumption, through the emergence of alternative food chains in the south of Brazil, more specifically in the northern coast of Rio Grande do Sul. Those networks are based on food that derive their value from their spatial origin. In this context, a qualitative study was conducted between February and August 2007, on a sample of 32 respondents. The analysis performed reveals that alternative foods can express much more than the organic ones, which are clean and handmade. In addition, they have the ability to illustrate a way of local autonomy defense and a return to the fundamentals of quality. This quality is based on valuing local knowledge through the production and consumption. In this sense, this article provides the elements to propitiate the understanding of how producers and consumers are immersed in the social construction of markets based on their local knowledge, quality, proximity and mutual trust.